Preventing heat stress before the Tokyo olympic games, the case of open water - Pla, R.; Aubry, A. (British Journal of Sports Medicine, 2021)
Background A huge heat stress is expected during the Tokyo 2020 Olympic Games, especially for the open-water swimming event. Literature is scarce about the physiological responses to open-water swimming events in warm water.